Associations between social burden, perceived stress, and diurnal cortisol profiles in older adults: implications for cognitive aging - Pretscher, Anna; Kauzner, Saskia; Rohleder, Nicolas; Becker, Linda (European Journal of Ageing, 2021)
Stress can be a risk factor for mental and physical health. We investigated the role of social burden as a potential stressor in older age and its associations with cognitive aging (i.e., within the domains inhibition and cognitive flexibility of executive functioning). Eighty-three older adults (N = 38 male, mean age = 74.0 ± 5.7 years, body-mass index = 25.5 ± 4.1 kg/m2) aged 64 years or older participated. Cognitive flexibility and inhibition were assessed by means of a Trail-Making Test (TMT) and a Stroop task. Perceived levels of social burden and perceived stress in general were assessed via standardized questionnaires. Furthermore, diurnal cortisol profiles were assessed. Overall, older participants showed lower cognitive performance than the younger (both inhibition and cognitive flexibility; p < .044). However, this association did not remain significant when adjusting for multiple comparisons. Social burden was highly correlated with perceived stress, highlighting its importance as a stressor (p < .001). Furthermore, participants who reported higher levels of perceived stress showed lower performance in the TMT as a measure for cognitive flexibility (p < .001). Moreover, social burden was associated with cognitive flexibility, which was assessed by means of the TMT (p = .031). However, this association did not remain significant when using the adjusted α-level. Furthermore, we found that total diurnal cortisol output was a mediator for the relationship between age and inhibition, which was assessed by means of a Stroop task. At last, we found that the mediating role of cortisol interacts with social burden in the way that especially in younger age, high levels of social burden are associated with higher cortisol levels and, therefore, with lower cognitive performance. We conclude that it is important to consider social burden as an additional stressor in older age which is associated with cognitive agin
Keywords: Social burden; Cognitive aging; Executive functioning; Diurnal cortisol; Stress

Covid-19 bezogene Präventionsmaßnahmen und ihre Auswirkungen auf die psychische Gesundheit, Arbeitszufriedenheit und organisationales Commitment - Pretscher, Anna; Paul, Karsten (52. Kongress der Deutschen Gesellschaft für Psychologie, 2022)

COVID-19-Related Prevention Measures at the Workplace and Their Impact on Mental Health and Job Satisfaction - Pretscher, Anna; Paul, Karsten; Zechmann, Andrea (Zeitschrift für Arbeits- und Organisationspsychologie, 2025)

Did the COVID-19 restrictions frustrate the fulfillment of important psychological needs? – Longitudinal evidence - Pretscher, Anna; Paul, Karsten (37th Annual Conference of the European Health Psychology Society, 2023)

Frustration psychischer Bedürfnisse durch COVID-19-Restriktionen – Längsschnittliche Evidenz - Pretscher, Anna; Paul, Karsten; Moser, Klaus (53. DGPs-Kongress / 15. ÖGP-Konferenz, 2024)

Life satisfaction buffers the effects of inflammation on cognitive aging - Becker, Linda; Kauzner, Saskia; Pretscher, Anna; Rohleder, Nicolas (78th Annual Meeting of the American Psychosomatic Society: Conference canceled due to COVID-19, 2020)

Warum Arbeitslosigkeit die psychische Gesundheit beeinträchtigt - Pretscher, Anna; Paul, Karsten; Moser, Klaus (2024)

When friendship suddenly becomes dangerous – effects of life goals on prevention adherence during COVID-19 - Pretscher, Anna; Paul, Karsten (38th Annual Conference of the European Health Psychology Society, 2024)